Research on DNA Nanostructures Based on the Hybrid Chain Reaction for the Assignment Problem. (12th July 2021) - Wang, Risheng; Yin, Zhixiang; Yang, Jing; Yang, Xinmu; Tang, Zhen
Abstract : Nanostructures with information processing play an important role in many fields. It is an excellent approach to the application that DNA nanostructures represented by DNA origami molecules combine with the hybrid chain reaction. In this paper, the assignment problem is mapped to a combinatorial graph on the DNA origami substrate. The graph has several modules corresponding to the time efficiency matrix of the assignment problem. The starting chain of the corresponding module is hybridized with the hairpin structure of the starting point, and the corresponding module is opened to emit light. The feasible solution to the problem can be obtained by observing the light-emitting fluorescent numbers of the opened modules. The fluorescent numbers of all the opened modules are added up on the same origami substrate, then different opening methods in different test tubes are compared, and the optimal solution is obtained.